Foundations of Information and Knowledge Systems : 11th International Symposium, FoIKS 2020, Dortmund, Germany, February 17-21, 2020, Proceedings /: 11th International Symposium, FoIKS 2020, Dortmund, Germany, February 17-21, 2020, Proceedings. (2020) - Unknown
No abstract available